SCIENTIFIC AND THEORETICAL FOUNDATIONS OF TEACHING UZBEK SHORT STORIES IN PRIMARY SCHOOLS - Ergasheva Muyassar Anvarovna (Bright Mind Publishing, 2025)
Uzbek literary criticism, an important problem is the scientific and theoretical analysis of short stories, which are unique examples of prose, the study of the system of artistic characters and images in them. The artistic purpose, didactic features of Uzbek short stories, their analysis in full accordance with the requirements of modernity, their system of images and the problem of the artistic hero require a separate scientific study.
Keywords: Literary criticism, hero, education, short story, teacher, innovation.